Commitment of Higher Education Institutions to Sustainability Agenda: Evidences from GCC Countries - BYSTROV, ILYA; PANIGRAHI, SHRIKANT KRUPASINDHU (The journal of contemporary issues in business and government, 2021)
Many higher education institutions have committed to the sustainability issues, however still these commitments unable to result with desired changes. It is crucial to recognize the changes in the education system that enable the institutions to understand the concept of sustainability. From the content analysis for each GCC country (United Arab Emirates, Kingdom of Saudi Arabia, Qatar, Sultanate of Oman, Kuwait and Kingdom of Bahrain), with selected 10 higher education institutions the authors found that only 5% of the universities opted to use sustainability in their mission statements. The extended analysis of the vision statements, institutional goals and values widened commitment to sustainable development to 11.5%. Analysis also showed that mostly UN Sustainable Development Goals 1, 8 and 9 are addressed. Higher education institutions of GCC are slowly incorporating sustainable development values into their strategic statements. Universities may take decade for the implication of sustainability development. The depiction of sustainability scenarios through various policy implementations and incentive measures would provide university scholars, leaders and government policy to strategize future developments.